The Effect of Salinity Concentration on Proline Dehydrogenase (ProDH) Gene Expression and Proline Accumulation in Black Rice and Red Rice - Rudiyanto, Yosefine Fetik; Fanata, Wahyu Indra Duwi; Siswoyo, Tri Agus (Discoveries in Agriculture and Food Sciences, 2024)
The nutraceutical properties of the pigmented rice provide an opportunity to be widely cultivated. A tendency to grow rice on sub-optimal land such as saline soil is an alternative to support food security, but the adaptation under saline soil is still questionable. This study was performed to determine the stress resistance of black (var. Ketan Hitam), red (var. MS Pendek), and white rice (var. IR64) as a commercial variety through proline accumulation and Proline dehydrogenase (ProDH) expression under salinity stress and recovery. The results showed that salinity stress increased the proline content in rice plants, with var. IR64 rice and var. MS Pendek (red rice) accumulated the highest amounts of proline, and the expression of the ProDH in IR64 and MS Pendek was increased in the recovery phase. These results indicate the foundation for elucidating the mechanism response of black and red rice to salinity stress and recovery ability.